ANALISIS KEUNTUNGAN DAN PEMASARAN BENIH IKAN BAWAL DI BELITANG KABUPATEN OKU TIMUR - Hariyono (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2016)
The purpose of this research were to: (1) Determine the seed marketing strategy pomfret in District Belitangr when seen from the SWOT descriptive analysis, (2) analyzing the pomfret fish hatchery operations in the District Belitang advantageous in one production process. This research was conducted in the District OKU Belitang East District. This research was conducted in the District Belitang. Determining the location of the research done by purposive or deliberate, with the consideration that in one of the District who developed hatchery operations and market pomfret pomfret fish fry as well as the region has a considerable number of the population in the study criteria. Location data collection research has been conducted on the Moon May 2015 until completion. This study found that profits in the business pomfret fish hatchery gained acceptance Rp 20,305,551 and Rp 12,305,449 earned income of R / C in the hatchery operations pomfret at 2:50 this value is greater than 1 means that each RP 1 spent will get the reception is 2.50 and the B / C 1:50 this value is greater than zero, which means each RP 0 then it will get revenue of 1.50 so that the analysis value of R / C to B / C can be concluded that hatchery operations pomfret get scope for further gains.